Factoring as an alternative way in financing small and medium-sized firms (SMSF) - BOURAS, A (Journal of Human Sciences, 2002)
Dr. A. BOURAS  Dr. A. BOUDAHDépartement de GestionFaculté desSciences Economiqueset Sciences de GestionUniversité MentouriConstantine, Algérie  The issue in financing firms is still raised by both professionals and academic researchers, where the degree of treatment may differ from a firm to a firm. The world of finance distinguishes between two types of firms: large, and small and medium ones. Small and Medium Sized Firms (SMSF) are still struggling to keep their activities growing and sustainable in the market place.Historically speaking, banks were merely the only way for financing SMSFs’ activities. However, new sources of finance have emerged, and have become more crucial, from which factoring is now being considered as an efficient way in financing the working capital of SMSF. The Algerian financial system is still far away from using factoring as a means of finance, although law and regulation have asserted it.